2005
DOI: 10.1002/ejic.200400392
|View full text |Cite
|
Sign up to set email alerts
|

A New Organic‐Inorganic Hybrid Gallophosphate Prepared in the Presence of Glycine

Abstract: A new layered gallophosphate, Ga 4 P 4 O 16 (C 2 H 5 NO 2 ) 4 , known as Mu-32 has been synthesised hydrothermally using the amino acid glycine (H 2 NCH 2 CO 2 H) as an original template. Such a template has never been used before for the synthesis of microporous and phosphate-based materials such as gallophosphates. The structure was determined by a single-crystal X-ray diffraction study and further characterised by scanning electron microscopy, elemental and thermal analyses and by 13 C and 31 P solid-state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
(16 reference statements)
1
8
0
1
Order By: Relevance
“…505 The layered gallophosphate Ga 4 P 4 O 16 (EtNO 2 ) 4 (MU-32) was studied by 1 H, 13 C and 31 P MAS NMR spectroscopy. 506 Similar data were reported for the novel species Ga 13 (PO 4 ) 18 (C 6 H 14 N) 13 507 6 ] Á 8H 2 O, where L = 1,4-dimethylpiperazine. 508 19 F, 31 P and 71 Ga MAS NMR spectra gave structural information for a hybrid open-framework fluorinated gallium oxalate-phosphate templated by 1,3-diaminopropane.…”
Section: Aluminiumsupporting
confidence: 79%
“…505 The layered gallophosphate Ga 4 P 4 O 16 (EtNO 2 ) 4 (MU-32) was studied by 1 H, 13 C and 31 P MAS NMR spectroscopy. 506 Similar data were reported for the novel species Ga 13 (PO 4 ) 18 (C 6 H 14 N) 13 507 6 ] Á 8H 2 O, where L = 1,4-dimethylpiperazine. 508 19 F, 31 P and 71 Ga MAS NMR spectra gave structural information for a hybrid open-framework fluorinated gallium oxalate-phosphate templated by 1,3-diaminopropane.…”
Section: Aluminiumsupporting
confidence: 79%
“…These encompass structures of isolated units, chains, layers, and frameworks, most of which represent their own unique structure type (although a few isotypic structures are found, as can be seen from the unit cell parameters in Table 4.3). For instance, the layers in phosphato-glycine-gallium (Hasnaoui et al 2005) differ significantly from those found in sulfato-glycinedi-lithium (Fleck and Bohatý 2004;Fig. 4.7).…”
Section: Other Glycine Saltsmentioning
confidence: 94%
“…8, 9 After the synthesis, it is observed in the pores of the material and can sometimes be bound to the inorganic framework via T-N or T-O-C bonds (T = Zn, Ga, ...). [9][10][11][12] Such connections between inorganic and organic parts are also observed in the oxalatephosphate systems (Ga-O-C bonds) and for phosphonate materials where a P atom is directly linked to a carbon atom (belonging to R group) in PO 3 R. 13,14 Histidine is one of the essential amino acids. In the monomeric form, it is a polydentate ligand which can coordinate to metal centers (e.g., Zn, Cu, Ni, Co, V) through the imidazole, the amino, and/or the carboxyl groups.…”
Section: Introductionmentioning
confidence: 99%